Implementation of Handmade Credit Agreements (Without Notary Deed) - Rikha Farikhatul Fitriani; Taufan Fajar Riyanto (Sultan Agung Notary Law Review, 2020)
The complete study, entitled "Implementation of Under-Handed Credit Agreements (Without Notary Deed) at PT. Central Java Bank, Semarang Regional Deposit of Sub-Branch "in order to find out and analyze the credit implementation process made under hand (without a Notary deed) at PT. Regional Development Bank of Central Java, Semarang Regional Deposit Assistant branch and to identify and analyze inhibiting factors in the implementation of loans made under hand (without a Notary deed) and how to overcome them. This study uses an empirical juridical approach, which is a legal research carried out by examining and analyzing existing facts in line with observations in the field. Central Java Regional Development Bank, Semarang Regional Deposit of Sub-Branch, for credit application will be given a Loan Application Certificate (SKPP) to be filled in completely and accompanied by the required documents / letters. The credit process "officially" begins with the submission of the completed form. Completely and correctly, all received credit applications will be analyzed and evaluated for credit. Guarantee transactions are carried out to conduct checks and research. The results of the analysis and evaluation, the transaction officer will report to the credit provider officer to refuse credit. Based on the results of the guarantee transaction, the credit provider officer analyzes the credit and the conclusion from the analysis is the adequacy of the guarantee, and for credit decisions accepted. Constraints that occur in the implementation of loans made underhand at PT. The Central Java Regional Development Bank for the Sub-Branch of the Semarang Region Regional Deposit to the community is largely a factor in providing credit guarantees in the form of land certificates of ownership rights (SHM) or Building Use Rights (SHGB) certificates that must be owned by prospective debtors themselves. Many prospective debtors have land assets that are still in the form of meters C and meters D so that the land cannot be pledged as collateral for credit. Settlement in overcoming constraints in implementing credit for PT. Bank Central Java Regional Deposit of Sub-Branch Offices are carried out by means of Bank officers assisting the management of the Property Rights Certificate to the National Land Agency (BPN) and continuing to provide outreach to candidates when customers apply for credit, while efforts to overcome the Bank's efforts to resolve bad loans this is the debtor in default, the Bank may first settle by way of kinship or by way of deliberation, if this fails, the Bank may issue a warning letter or warning letter in the form of administrative sanctions.